The Role Of The Family Environment In Early Childhood Learning In Talunpring Hamlet, Lamongan District - Putri, Dita Ngandika; Hendrawijaya, Arief Tukiman; Purnamawati, Frimha; Chanif, Arini Milla (SPEKTRUM: Jurnal Pendidikan Luar Sekolah (PLS), 2025)
The family environment has an important role in supporting children's development, especially in the initial education provided by parents. Based on Vygotsky's sociocultural theory, children's development is influenced by social interactions and the culture around them, making learning a social process. This research aims to describe the role of the family in early childhood learning in Talunpring Hamlet, Lamongan Regency. Using a descriptive qualitative approach, data was collected through observation, interviews and documentation. Informants were determined using purposive sampling, consisting of 5 key informants and 2 supporters. Data validity is carried out through extended observations, increased persistence, and triangulation. Data analysis is carried out through reduction, data presentation and drawing conclusions. The research results show that the family has played a role as a guide and motivator, especially in learning through play and developing character values, even though the approach used is still simple. However, families do not fully understand the principles of learning that are oriented towards child development, so the approach applied is not appropriate to the child's development stage. Apart from that, the role of the family as a facilitator in providing learning facilities and resources at home is still limited